Neue Scolytoidea aus Brasilien. 172. Beitrag zur Morphologie und Systematik der Scolytoidea (Coleoptera). - Schedl, Karl Eduard (Contributions to Entomology = Beiträge zur Entomologie, 1959)
From material collected by F. Plaumann in Nova Teutonia (Brazil) and forwarded to the Deutsches Entomologisches Institut for preparation the author describes in a first contribution 1 new genus, 12 new species and the hitherto unknown male or female of 4 species of Scolytoidea. Nomenclatural Acts sulcatus Schedl, 1959 (Breviophthorus), spec. n. rufulus Schedl, 1959 (Chiloxylon), spec. n. granulipennis Schedl, 1959 (Chramesus), spec. n. unimodus Schedl, 1959 (Cryptocleptes), spec. n. dubius Schedl, 1959 (Hylocurus), spec. n. interruptus Schedl, 1959 (Hylocurus), spec. n. brasiliensis Schedl, 1959 (Phrixosoma), spec. n. dimorphus Schedl, 1959 (Pityophthorus), spec. n. immunis Schedl, 1959 (Platypus), spec. n. propinquus Schedl, 1959 (Platypus), spec. n. gracilior Schedl, 1959 (Pterocyclon), spec. n. Chiloxylon Schedl, 1959 (Scolytidae), gen. n. grandis (Schedl, 1954) (Thamnophthorus), comb. n. hitherto Neodryocetes grandis Schedl, 1954